More Rooms, Less Profit: Unveiling OTA Distribution Channels' Contradictory Hotel Impacts - I Gusti Made Juniarta; Cing Cing Wahyuni; Pungky Dios Purnomo; Dyah Palupiningtyas (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This research aims to evaluate the effectiveness of Online Travel Agent (OTA) distribution channels in influencing room sales volume and net profit for hotels in Java. Although OTAs have become a primary distribution choice that successfully boosts sales figures, there is still a lack of research highlighting the impact on net profitability due to high commission costs.Using a quantitative associative method through panel data regression analysis, this study examines the causal relationship between the proportion of sales made via OTAs and two performance indicators over a two-year period (2021–2023). The primary findings reveal a dual effect:OTA Distribution Channels have a positive and significant influence on Room Sales Volume (supporting Hypothesis H1).Conversely, OTAs have a significant negative impact on Hotel Profit Margins (supporting Hypothesis H2), indicating a substantial financial trade-off.The contribution of this research is to provide balanced empirical evidence regarding volume gains versus margin losses resulting from OTA usage. The managerial implications suggested by these findings are that hotels need to implement distribution strategies focused on Net Revenue Management and channel mix optimization to achieve a balance between volume requirements and profitability.